The application of web 2.0 tools to determine Malay AFL-learners’ performances in receptive skills - Aliyu, Abdullahi; Nurazan, Mohmad Rouyan; Siti Salwa, Mohd Noor; Ibrahim, Bashir (2018)
The application of modern technologies in educational fields thrills with a sudden shift in using of the internet from Web 1.0 to Web 2.0 in the early 21st century. In the time various technological tools and social media sites evolved for social, entertainment and educational purposes. The application of such technological tools in teaching and learning of a language is termed computer-assisted language learning. This study aims to determine the performance of Malay undergraduate learners of Arabic as a foreign language at UinSZA in reading, and listening skills using the online tool "QuizCreator Online”. The sample of the study comprises 30 Malay Undergraduate students that are learning Arabic as a foreign language at UniSZA. The data of the study are collected through test instrument designed and marked based on TOAFL (AL-ARABIA) marking scheme deployed into “QuizCreator Online”. The results indicated that only 7 participants scored pass points in reading skill test and 8 participants in listening skill test. In reverse case, 23 participants failed reading skill test and 22 participants in listening skills test. The results indicated the passing rate in reading skills test as 28.35 % and 29.21 % in listening skills test. This study recommends the use of web 2.0 tools such as Blogs, Edmodo, Facebook and QuizCreator Online tools teaching and learning of Arabic language to Maly AFL learners.